(untitled) (Journal of Engineering, 2024)
Human activities such as mining, industrial operations and waste management can lead to soil pollution by heavy metals including chromium, cadmium, mercury, lead and arsenic. These contaminants cause harm both to humans and the ecosystems where they are found. Of all the previously used techniques, phytoremediation is the most promising one for cleaning up heavy metal-contaminated soils. Phytoremediation refers to a technique where plants use roots for absorbing, storing and immobilizing soil contaminants while also removing them. Bioleaching is a method which uses microorganisms to dissolve metals that have been shown to facilitate phytoextraction in increasing the availability of metals. It is anticipated that research advancements and technological innovations will make it more efficient and appropriate. Root absorption is increased by bioleaching through modification of rhizosphere thus making it more bioavailable for plant uptake. Plant-bacterial interactions are proven to speed up the remediation rates. Both processes can help clear off pollutants from the soil environment. However, further research is needed to find and improve the best strains of microorganisms, assess long-term soil impacts and control massive influxes of bacteria. The combination of bioleaching and phytoextraction offers a reliable and efficient system for removing metals from polluted soils.